Spatial and seasonal occurrence of micropollutants in four Portuguese rivers and a case study for fluorescence excitation-emission matrices - Marta O. Barbosa (2018)
The European Union (EU) has recommended the monitoring of specific priority substances (PSs, Directive 2013/39) and some contaminants of emerging concern (CECs, Decision 2015/495) in surface waterbodies. The present study provides spatial distributions and temporal variations of a wide range of multi-class PSs and CECs in four stressed rivers in Portugal (Ave, Leca, Antua, and Certima). Thirteen micropollutants were found in all four rivers, including the priority pesticide isoproturon (up to 92 ng L-1), various pharmaceuticals (up to 396 ng L-1), and the UV-filter 2-ethyl-hexyl-4-methoxycinnamate (EHMC, up to 562 ng L-1) identified in Decision 2015/495. The industrial priority compound perfluorooctanesulfonic acid (PFOS) was found in three rivers (Antua, Certima, and Leca) below the method quantification limit, together with four pharmaceuticals not included in these EU guidelines. The already banned priority pesticide atrazine was detected in Ave, Antua, and Leca (up to 41 ng L-1) and simazine in Certima and Leca (up to 26 ng L-1). Acetamiprid and imidacloprid (included in Decision 2015/495) were only detected during the dry season in the Ave. Leca river was selected as a waterbody case study for assessment of fluorescence excitation-emission matrices (EEMs). These results matched the spatial distribution trend of micropollutants along the river, with stronger fluorescence response and higher concentrations being found downstream of industrial areas and urban waste water treatment plants (WWTPs). Moreover, the fluorescence signature of surface water collected downstream of an urban WWTP aligned very well with that obtained for the respective WWTP effluent. Thus, actions are needed to preserve a good environmental status of these stressed European waterbodies.